Learning the Lessons of Antitumour Necrosis Factor Therapy-Associated Psoriasis - Matt Shale; Subrata Ghosh (Canadian Journal of Gastroenterology)
Psoriasis or psoriasiform skin lesions, as an adverse effect of treatment with antitumor necrosis factor antibody therapy, have been described relatively recently. Patients with these lesions have no personal or family history of psoriasis. In a small number of cases, an association with Chlamydia has been suggested. The skin lesions may disappear on discontinuation of therapy or, in the majority of cases, even if antitumor necrosis factor antibody therapy is continued. Therefore, withdrawal of therapy is generally not required for this adverse effect but referral to a dermatologist may be desirable for confirmation of diagnosis and treatment.